Development of BPJS from Participation, Government Policy, and Technological Aspects After Pandemic - Ainur Basirah Mulya; Nurmiati Liska Suspenny; Cucu Wayamah; Erlina Puspitaloka Mahadewi (CV. Inara, 2025)
The pandemic hits all sectors, not only public health but also economic, financial and social aspects. The pandemic in the past makes health development in Indonesia necessary, especially because of its impact on the development of health insurance. Health insurance exists in the form of health protection guarantees, so that participants receive health care benefits, and basic health needs protection is provided to anyone who has paid the insurance premium. The package offered by the National Health Insurance Scheme (JKN) Indonesia goverment is very comprehensive, and includes promotional, preventive, curative and rehabilitative services, all of which are covered and free of charge. Limit costs if they comply with procedures. The JKN program is organized by the Social Health Security Administration (BPJS). Many changes have been made to BPJS in the wake of the Covid-19 pandemic, both in terms of BPSJ membership, government regulations and the technology sector in Indonesia. The methodology of this study is a literature review using international and domestic publications through various databases of research articles, reports and research documents to explain the transition of health insurance to Indonesia after the Covid-19 pandemic. The purpose of this study is to highlight the changes that have occurred in national health insurance, especially BPJS, due to the Covid-19 pandemic. This may add new knowledge that the history of health insurance development in Indonesia was caused by the pandemic disaster and after pandemic.